Immunomodifiers in combination with conventional chemotherapy in small cell lung cancer: a Phase II, randomized study - Zarogoulidis K; Ziogas E; Boutsikou E; Zarogoulidis P; Darwiche K; Kontakiotis T; Tsakiridis K; Porpodis K; Latsios D; Chatzizisi O; Karapantzos I; Li Q; et al. (Dove Medical Press, 2013)
Konstantinos Zarogoulidis,1 Eftimios Ziogas,1 Efimia Boutsikou,1 Paul Zarogoulidis,1,2 Kaid Darwiche,2 Theodoros Kontakiotis,1 Kosmas Tsakiridis,3 Konstantinos Porpodis,1 Dimitrios Latsios,1 Olga Chatzizisi,4 Ilias Karapantzos,5 Qiang Li,6 Georgios Kyriazis21Pulmonary Department, "G Papanikolaou" General Hospital, Aristotle University of Thessaloniki, Thessaloniki, Greece; 2Department of Interventional Pneumology, Ruhrlandklinik, West German Lung Center, University Hospital, University Duisburg-Essen, Essen, Germany; 3Thoracic Surgery Department, "Saint Luke" Private Hospital, Panorama, Thessaloniki, Greece; 4Immunology Department, "G Papanikolaou" General Hospital, Aristotle University of Thessaloniki, Thessaloniki, Greece; 5Ear, Nose and Throat Department, "Saint Luke" Private Hospital, Panorama, Thessaloniki, Greece; 6Respiratory Diseases Department, Shanghai hospital, Second Military Medical University, Shanghai, People's Republic of ChinaPurpose: To evaluate the effect of immunotherapy on response, survival, and certain immune markers in patients with small cell lung cancer (SCLC) who are receiving chemotherapy.Patients and methods: Patients with SCLC (n = 164) were assigned to receive either chemotherapy alone (group A) or a combination of chemotherapy and immunotherapy as follows: interferon α (IFN-α; 3 million IU) 3 times per week (group B); IFN-γ (3 million IU) 3 times per week (group C); and IFN-α and IFN-γ (1.5 million IU of each) 3 times per week (group D). Chemotherapy was the same for all groups and consisted of eight cycles with carboplatin 5.5 mg/m2 intravenously on day 1, ifosfamide 3.5 mg/m2 intravenously on day 1, and etoposide 200 mg/m2 total dose taken orally on days 1 through 3, every 28 days. Patients completing chemotherapy were restaged, and those who were found to have limited disease received primary site and prophylactic cranial irradiation. Immunotherapy was continued throughout these treatments and during the follow-up period. Blood was taken before each course of chemotherapy and during follow-up to measure CD3+ lymphocytes, CD3+CD4+ lymphocytes, CD3+CD8+ lymphocytes, natural killer cells, and natural killer T cells.Results: Differences in response and survival were not significantly different when all patients were considered. However, among patients with limited disease, Kaplan–Meier analysis disclosed a survival benefit for group B (P < 0.05). The analysis of immunologic measurements revealed that the improvement of immune markers was always accompanied by clinical improvement, whereas deterioration of all markers was accompanied by disease progression (result not statistically significant except for group C; P < 0.05).Conclusion: Among cytokines used in the study, only IFN-α seems to confer a survival benefit to patients with SCLC with limited disease. However, immunotherapy remains a challenge in the treatment of lung neoplasms and should be further explored.Keywords: interferon, SCLC, lung cancer, immunomodifiers